Simbiosis TV free to air Dengan Situs Web Berbagi Video (Studi kasus TV Jakarta yang mengalihkan konten ke saluran YouTube) - Algooth Putranto; Arsa Widitiarsa Utoyo (VISIONER : Jurnal Komunikasi, Bisnis dan Konten Kreatif, 2019)
This study discusses television media policy as an old media that looks at new media trends, participates in the flow of trends by using new media as a means of disseminating the material owned, attracting viewers and reaping the benefits of new media. On the other hand, this television policy has a direct impact on the television broadcast regulator, the Indonesian Broadcasting Commission (KPI), which has no authority over content on the internet. The researcher took the main case to be analyzed, namely the Jakarta-based free to air television and the attitude of the Central KPI commissioner. The core theory determinism is the discovery or development of communication technology is a factor that changes human culture. The discovery or development of communication technology is what actually changes human culture. If Karl Marx assumed that history was determined by the power of production, then according to McLuhan human existence was determined by changes in modes of communication. Changes in modes of communication form a culture by going through several stages, namely, discoveries in communication technology lead to cultural change, changes in the types of communication shape human life and how the tools for communication affect our own lives. On the other hand, the transition of content from conventional television to the YouTube channel directly reduces the role of the KPI that shares public power in the supervision of broadcast content as a spirit of Reformation, with the transition of broadcast content to the YouTube channel precisely returning the role of supervision and enforcement to the Government through number law. 11 of 2008 concerning electronic information and transactions.